Implementation of Sustainable Reforms in the Indian Automobile Industry: From Vehicle Emission Perspective - Jai Prakash (Innovative Research Thoughts, 2022)
The Indian car sector must address vehicle emissions and adopt sustainable changes to change its direction. The environmental impacts of rapid urbanisation and economic progress have increased automobile ownership in the country. Comprehensive measures are needed to reduce emissions and promote sustainability. Multifaceted reforms underpin them. First, the Indian government must set global-standard emission regulations and thoroughly monitor compliance. This requires tight coordination between regulators and automakers to produce cleaner, greener automobiles. A thorough emissions testing and certification system is needed to validate vehicle performance in real life. Equally important is switching to greener fuels. Promotion of electric vehicles (EVs) is transformational. Tax incentives, subsidies, and charging infrastructure may motivate EV adoption, making them accessible to the public. Renewable energy sources in the grid boost EVs' environmental advantages and reduce their carbon footprint. Sustainable improvements go beyond cars. Rethinking urban planning and transportation is crucial. Investing in public transit, bike lanes, and pedestrian-friendly infrastructure reduces car use. Shared mobility services reduce traffic and optimise resource use, hence they should be promoted. Innovation relies on academics, research institutes, and industry collaboration. Research and development of battery technology, vehicle design, and alternative propulsion technologies may accelerate sustainable transportation. Encourage green tech businesses to bring new ideas and solutions to the ecosystem. raising customer awareness and education is crucial. Education regarding the environmental effect of transportation may drive demand for eco-friendly alternatives.